La réforme pénale au Canada : l’apport de la Commission canadienne sur la détermination de la peine - Pires, Alvaro (Criminologie, 1987)
This study is a critical analysis of the penal reform project put forward by the Canadian Commission on Sentencing from the point of view of moderation. The author first considers the Commission's position in the penological debate between the Medical Model and the Justice Model. He then analyses the “new theory on sanctions” proposed by the Commission, as well as its position on “community measures” and on the ideal of rehabilitation. Finally, his analysis focuses on a number of the Commission's major recommendations for reform, its policy in terms of maximum and minimum sentences, the new “exceptional sentence” (intended to replace the present measures regarding “dangerous criminals”), its position on imprisonment of “twenty-five years' minimum” and its general guidelines for Canada. In conclusion, the author make an evaluation of the orientation of the Commission's reform with respect to the principle of moderation.